(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
Today, globalization and integration processes are increasing all over the world, and Uzbekistan is no exception. Not only in international relations, but also in the domestic environment, in building a stable and prosperous society, the greening of residential areas, recreation avenues, parks, district and city areas with decorative trees, bushes, which have a positive effect on the environment, Great attention is being paid to the breeding of ornamental trees.